Immune checkpoints programmed death 1 ligand 1 and cytotoxic T lymphocyte associated molecule 4 in gastric adenocarcinoma. (3rd May 2016) - Schlößer, Hans A.; Drebber, Uta; Kloth, Michael; Thelen, Martin; Rothschild, Sacha I.; Haase, Simon; Garcia-Marquez, Maria; Wennhold, Kerstin; Berlth, Felix; Urbanski, Alexander; Alakus, Hakan; Schauss, Astrid; et al.
ABSTRACT: Remarkable efficacy of immune checkpoint inhibition has been reported for several types of solid tumors and early studies in gastric adenocarcinoma are promising. A detailed knowledge about the natural biology of immune checkpoints in gastric adenocarcinoma is essential for clinical and translational evaluation of these drugs. This study is a comprehensive analysis of cytotoxic T lymphocyte associated molecule 4 (CTLA-4) and programmed death 1 ligand 1 (PD-L1) expression in gastric adenocarcinoma. PD-L1 and CTLA-4 were stained on tumor sections of 127 Caucasian patients with gastric adenocarcinoma by immunohistochemistry (IHC) and somatic mutation profiling was performed using targeted next-generation sequencing. Expression of PD-L1 and CTLA-4 on lymphocytes in tumor sections, tumor-draining lymph nodes (TDLN) and peripheral blood were studied by flow-cytometry and immune-fluorescence microscopy in an additional cohort. PD-L1 and CTLA-4 were expressed in 44.9% (57/127) and 86.6% (110/127) of the analyzed gastric adenocarcinoma samples, respectively. Positive tumor cell staining for PD-L1 or CTLA-4 was associated with inferior overall survival. Somatic mutational analysis did not reveal a correlation to expression of PD-L1 or CTLA-4 on tumor cells. Expression of PD-1 (52.2%), PD-L1 (42.2%) and CTLA-4 (1.6%) on tumor infiltrating T cells was significantly elevated compared to peripheral blood. Of note, PD-1 and PD-L1 were expressed far higher by tumor-infiltrating lymphocytes than CTLA-4. In conclusion, specific immune checkpoint-inhibitors should be evaluated in this disease and the combination with molecular targeted therapies might be of benefit. An extensive immune monitoring should accompany these studies to better understand their mode of action in the tumor microenvironment.